An exploratory analysis of linking adverbials in post-secondary texts from L1 Arabic, Chinese, and English writers. (2020) - Appel, Randy
Abstract: Linking adverbials (e.g., in addition, however) are an important aspect of discourse cohesion. However, our understanding of how these items are used by post-secondary writers is lacking, particularly as it relates to potential L1-related production differences. The current research aims to better understand how writers from three different language backgrounds (Arabic, Chinese, English) make use of linking adverbials in their academic English writing. Quantitative and qualitative methods were used to assess production differences for linking adverbials in the writing of each L1 using a collection of 240 essays. Findings include general overuse (types and tokens) by L2 users, overuse of listing and appositional devices by L1 Arabic writers, overuse of contrastive and transitional linking adverbials by L1 Chinese writers, and underuse of summative items by L1 English writers. Pedagogical and methodological implications of these findings are discussed. Highlights: 3-way analysis of linking adverbials in the academic English essays of L1 Arabic, Chinese, and English writers. General overuse of linking adverbials (types and tokens) by both groups of EFL writers. Comparative overuse of listing and appositional functional categories by L1 Arabic writers. Comparative overuse of contrastive and transitional functional categories by L1 Chinese writers. Comparative underuse of the summative functional category by L1 English writers.